Comparison of access to medicines between Klang Valley and East Coast of peninsular Malaysia for children living in poor households - Saiful, A; Ithnin, M; Rani, MDM; Mohamed, IN; Al-Naggar, R; Nor Azila Noh; Nazefah Abdul Hamid; Khairun Nain Nor Aripin (Pharmacotherapy Group, 2024)
Indexed by WOS/Scopus